Hubungan Pola Asuh Otoriter terhadap Kesehatan Mental Remaja - Andini Septia Irsanin (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Parenting style is one of the methods used by parent to care for and guide children in various ways so that children become adults in accordance with societal norms. The low role of the family in raising children can cause mental health problems in adolescents. This study aims to determine the relationship between authoritarian parenting style and adolescent mental health with the research sample, namely students aged 15-18 years who attend SMK Negeri 6 Surakarta. This research uses a quantitative approach. The data collection method uses two types of scales, namely the authoritarian parenting style scale and the mental health scale. The data analysis technique used is hypothesis testing with product moment correlation analysis. The research result show that there is a relationship between authoritarian parenting and adolescent mental health. This is know from the product correlation test result of 0,117 ≥ 0,005. The higher the authoritarian parenting style of parent, the lower the mental health experienced by teenagers